The Atlantic–Mediterranean ecological connection: a study on decapod larval communities - PIRES, RITA F.T.; PAN, MARIA; CATALÁN, IGNÁCIO A.; PRIETO, LAURA; SANTOS, MIGUEL P. P.; FARIA, CLÁUDIA; FERREIRA, SUSANA; SANTOS, ANTONINA DOS (Mediterranean Marine Science, 2018)
Larval dispersal mechanisms, although significantly studied, are far from being completely resolved. Local studies are needed to clarify key interactions between individual life cycles and transport processes. The Atlantic-Mediterranean connection through the Strait of Gibraltar is a particularly important area to explore these processes, as a hotspot for detecting species fluxes and/or invasions between several Large Marine Ecosystems. However, the area dynamics and the mechanisms used by larvae to cope with the system hydrological conditions are scantly explored. Summer data on decapod larvae and ocean water masses from an extended area of the southern Portugal, Gulf of Cadiz, Strait of Gibraltar and Alboran Sea were analyzed, and the larval assemblages and their potential retention/dispersal mechanisms were explored. Different larval assemblages were linked to the hydrological conditions of each basin. Shelf width differences and its influence in along/cross-shore transport were the main drivers of decapod distribution, acting as biological barriers. Larvae of mesopelagic species dominated the northern Alboran Sea innershelf, highly influenced by offshore currents. Here, nearshore processes were limited to surface waters, while in the Gulf they extended more deeply and to the outer shelf. Results on species ecological traits can easily be applied to oceanographically similar areas of world coastal regions and could be used for further development of ecological modelling studies.